2012
DOI: 10.1128/aac.05116-11
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of IncA/C bla CMY-2 -Carrying Plasmids by Acquisition of the bla NDM-1 Carbapenemase Gene

Abstract: The bla NDM-1 gene has been reported to be often located on broad-host-range plasmids of the IncA/C type in clinical but also environmental bacteria recovered from the New Delhi, India, area. IncA/C-type plasmids are the main vehicles for the spread of the cephalosporinase gene bla CMY-2 , frequently identified in the United States, Canada, and Europe. In this study, we completed the sequence of IncA/C plasmid pNDM-KN carrying the bla NDM-1 gene, recovered from a Klebsiella pneumoniae isolate from Kenya. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
82
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 133 publications
(92 citation statements)
references
References 36 publications
6
82
0
Order By: Relevance
“…Similar to the aforementioned IncN2 bla NDM-1 genetic contexts, the IncA/C bla NDM-1 genetic context was also observed within two different species within the same patient (patient 4). Further, it is very similar to the most frequently reported IncA/C bla NDM-1 genetic context of the Enterobacteriaceae family (8,14,31). The combination of IncA/C bla NDM-1 genetic context identification (Fig.…”
Section: Figsupporting
confidence: 54%
“…Similar to the aforementioned IncN2 bla NDM-1 genetic contexts, the IncA/C bla NDM-1 genetic context was also observed within two different species within the same patient (patient 4). Further, it is very similar to the most frequently reported IncA/C bla NDM-1 genetic context of the Enterobacteriaceae family (8,14,31). The combination of IncA/C bla NDM-1 genetic context identification (Fig.…”
Section: Figsupporting
confidence: 54%
“…Molecular epidemiological studies indicated that the IncA/Ctype broad-host-range plasmids associated with mosaic genetic structures (e.g., ISAba1) are mainly responsible for spreading bla NDM-1 among the Enterobacteriaceae (4,33). Moreover, the IncFII, IncN, IncH, and IncL/M types of plasmids have also been associated with bla NDM (34)(35)(36).…”
Section: Resultsmentioning
confidence: 99%
“…The bla NDM-1 gene was originally identified among Klebsiella pneumoniae isolates from infections originating in India. However, it was quickly realized that this gene was plasmid borne, was present on multiple plasmid types ( [164][165][166][167], and was rapidly spreading between bacteria (168). The first report of bla NDM in Salmonella involved a patient with a Klebsiella pneumoniae infection that was resistant to carbapenems (169).…”
Section: Role Of Plasmids In Salmonella Genome Evolutionmentioning
confidence: 99%